PENGARUH RETURN ON EQUITY, DEBT TO EQUITY RATIO, CURRENT RATIO, DAN OPINI AUDIT TERHADAP HARGA SAHAM PADA SUB-SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Victor Jonathan Hutabarat; Muyassaroh Muyassaroh (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2026)
This study aims to analyze the impact of Return on Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR), and Audit Opinion on the stock prices of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative approach was employed using secondary data, specifically audited annual financial statements and stock closing prices. The sample was selected using purposive sampling, resulting in 10 companies observed over five years, yielding 50 firm-year observations. Analysis was conducted using descriptive statistics, classical assumption tests, and multiple linear regression with the aid of SPSS. Partial test results indicate that ROE, DER, and CR have a positive and significant effect on stock prices, whereas Audit Opinion has a negative but insignificant effect. Simultaneous test results show that ROE, DER, CR, and Audit Opinion collectively have a significant effect on stock prices. These findings confirm that investors in the food and beverage sub-sector place greater weight on fundamental financial information than on audit opinions.Keywords: Return on Equity; Debt to Equity Ratio; Current Ratio; Audit Opinion; Share Price